2017
DOI: 10.18203/2320-6012.ijrms20173587
|View full text |Cite
|
Sign up to set email alerts
|

A clinical study of acute intestinal obstruction in adults-based on etiology, severity indicators and surgical outcome

Abstract: Background: Patients with bowel obstruction still represent some of the most difficult and vexing problems that surgeons face today. While the adage, “never let the sun rise or set on a bowel obstruction” remains true, there has been a trend towards selective non-operative management of this problem. Aims and objectives were to study the various causes and modes of presentation of intestinal obstruction and to evaluate the importance of different severity indicators of obstruction with early recognition, diagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 3 publications
1
20
0
Order By: Relevance
“…Intestinal obstruction (IO) is a potentially risky surgical emergency associated with high morbidity and mortality rates in both developed and developing world [1, 2]. It also causes significant surgical side effects in hospital admissions and adversely affects the life of millions of people, cutting across all age groups, with considerable direct and indirect economic impacts on the healthcare system and the affected patients [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intestinal obstruction (IO) is a potentially risky surgical emergency associated with high morbidity and mortality rates in both developed and developing world [1, 2]. It also causes significant surgical side effects in hospital admissions and adversely affects the life of millions of people, cutting across all age groups, with considerable direct and indirect economic impacts on the healthcare system and the affected patients [3].…”
Section: Introductionmentioning
confidence: 99%
“…Based on the anatomical location, IO is mainly classified as small bowel obstruction (SBO) and large bowel obstruction (LBO) [2]; it can also be either mechanical or functional on the basis of the underlying pathophysiology of obstruction [11]. The etiology of IO has been varied with SBO caused by adhesions, strangulated hernia, malignancy, and volvulus [2]. The causes of IO also vary in different populations and areas.…”
Section: Introductionmentioning
confidence: 99%
“…Taneja et al report shows 90% of cases with multiple air fluid level and Savage et al reports 95% cases with significant findings. Tiwari SJ et al 21 reported multiple air fluid levels in 70% patients. Suri et al 22 reported 77% sensitivity and 50% specificity of x-ray in the diagnosis of intestinal obstruction.…”
Section: Imagingmentioning
confidence: 98%
“…Jancelewicz et al 25 found that decreased bowel wall enhancement on CT, leucocytosis, and peritoneal signs were the only independent predictors of strangulation obstruction on a multiple logistic regression analysis. Tiwari SJ et al 21 reported multiple air fluid levels in 70% patients. Suri et al 22 reported 93% sensitivity and 100% specificity of CT-scan in the diagnosis of intestinal obstruction.…”
Section: Imagingmentioning
confidence: 98%
“…1 12-16% of acute abdominal emergencies may be contributed to intestinal obstruction. 2 The etiology of bowel obstruction has been varied with small intestinal obstruction caused by adhesions in 60% , strangulated hernia in 20%, malignancy in 5% and volvulus in 5%. 2 The timing of surgical intervention putting in mind possibility of Intestinal Ischemia (strangulation) is important which needs urgent exploration.…”
Section: Introductionmentioning
confidence: 99%